Research Progress of PPR Proteins in RNA Editing, Stress Response, Plant Growth and Development - Qin, Tengfei; Zhao, Pei; Sun, Jialiang; Zhao, Yuping; Zhang, Yaxin; Yang, Qiuyue; Wang, Weipeng; Chen, Zhuanqing; Mai, Tengfei; Zou, Yingying; Liu, Guoxiang; Hao, Wei (Frontiers in Genetics, 2021)
RNA editing is a posttranscriptional phenomenon that includes gene processing and modification at specific nucleotide sites. RNA editing mainly occurs in the genomes of mitochondria and chloroplasts in higher plants. In recent years, PPR proteins, which may act as trans-acting factors of RNA editing, have been identified, and the study of PPR proteins has become a research focus in molecular biology. The molecular functions of these proteins and their physiological roles throughout plant growth and development are widely studied. In this minireview, we summarized the current knowledge of the PPR family, hoping to provide some theoretical reference for future research and applications.